New Dialectics and Political Economy
XIX, 218 p.
Keywords: Many of the leading thinkers on dialectics in the Marxian tradition have collaborated here to put forward and debate challenging new perspectives on the nature and importance of dialectics. The issues dealt with range from the philosophical consideration of the precise nature of dialectical reasoning, to dialectics and economic theory, and to more concrete concerns such as how dialectics can help us think about globalization, freedom, inflation and subjectivity.